Blockchain technology use case in supply chains in transport hubs - Li Binzhang (Вестник СибАДИ, 2022)
Introduction. Efficient freight transport and management in large transportation hubs is crucial to world trade. Existing freight management systems fail to ensure traceability, transparency, information security and consistency of data stored and exchanged during the various operational processes. As a result, this has a negative impact on the performance of transport hubs.Materials and methods. The use of digital information and communication technology (ICT) applications in the transport industry can lead to highly automated processes and more cost-effective solutions. Freight transport requires the use of real-time data exchange between different stakeholders involved in the process. Traditional ICTbased logistics systems use a centralised architecture to host and process data and services. However, centralized logistics systems cannot ensure secure access to real-time data, operational visibility and trust between participating organisations.Results. Automation of various transport hub functions using the Internet of Things (IoT) and cloud computing can adequately improve the performance of transport hub operations. These operations include automation of vehicle interface, container yards, intra-port logistics and terminal receiving point.Discussion and Conclusions. In this paper, we have explored opportunities for process improvement by integrating information exchange between different actors using end-to-end technologies in transport hubs, in particular the concept of blockchain, to optimise operations in international trade by integrating and sharing information between actors in the transport process.